Assessing EFL Students’ Direct and Indirect Speech Mastery - Ida Ayu Oka Purnami; Ni Luh Putu Ning Septyarini Putri Astawa (STKIP Yapis Dompu, 2020)
The present study was aimed to assess Direct and Indirect Speech Mastery of the Senior High School Students of Piloting School in Gianyar. The study was intended to find out to what extent is the assessing direct and indirect speech mastery of the eleventh grade students. The study used an ex-post facto research design or non-experimental research design. In order to answer the research question, the data required for the study were collected by administering the research instruments in the form of transformation test items. The population of the study is the eleventh grade students of Piloting School consisting of 184 students all together. There were 40 students determined as the sample of the study by using systematic random sampling method. The results of the data analysis that were analyzed by using norm-reference of five standard values clearly showed(1) There were 4 subject (10%) who showed excellent assessment of direct and indirect speech, (2) 7 subjects (17,5%) who showed good assessment, (3) 15 subjects (37,5%) who showed sufficient assessment, (4)12 subjects (30%) who showed insufficient assessment, (5) 2 subject (5%) who showed poor assessment. In general, these research findings showed that assessing direct and indirect speech mastery of the eleventh grade students of Piloting School in Gianyar was sufficient.